Topologically distinct Feynman diagrams for mass operator in electron-phonon interaction - Tovstyuk, C.C. (Condensed Matter Physics, 2009)
The new method for designing topologically distinct Feynman diagrams for electron's mass operator in electronphonon
interaction is developed using the permutation group theory. The carried out classification of DPs
allows to choose the classes, corresponding to disconnected diagrams, to singly connected diagrams, direct
( tadpole ) diagrams, to diagrams corresponding to phonon Green functions. After this classification the set of
considered double permutations is reduced to one class since only these are relevant to mass operator. We
derive analytical expressions which allow to identify the DP, and to choose the phonon components, which
are not accepted in every type. To avoid repetition of asymmetric diagrams, which correspond to the same
analytical expression, we introduce the procedure of inversion in phonon component, and identify symmetric
as well as a pair of asymmetric phonon components. For every type of DP (denoted by its digital encoding),
taking into account its symmetry, we perform a set of transformations on this DP, list all DPs of the type and
all the corresponding Feynman diagrams of mass operator automatically. It is clear that no more expressions
(diagrams) for the relevant order of perturbation theory for mass operator can be designed. Запропоновано новий метод побудови топологiчно нееквiвалентних дiаграм Фейнмана для масового оператора при електрон-фононнiй взаємодiї iз використанням методу подвiйних перестановок (ПП). Проведено класифiкацiю ПП, яка дозволяє визначити класи, що вiдповiдають незв’язаним, звiдним дiаграмам, прямим та дiаграмам, якi вiдповiдають функцiї Грiна фононiв. Проведена класифiкацiя дозволяє звузити кiлькiсть ПП, що розглядається, до одного класу, оскiльки саме вони вiдповiдають масовому операторовi. Отримано аналiтичний вираз, за допомогою якого записуються подвiйнi перестановки, та обираються фононнi компоненти, вiдсутнi для кожного типу. Щоби уникнути записiв не симетричних дiаграм, якi вiдповiдають однаковим аналiтичним виразам, вводиться операцiя iнверсiї у фононнiй компонентi i видiляються симетричнi та пари несиметричних фононних складових. Для кожного типу ПП (вiдображеного своїм цифровим зображенням) з врахуванням його симетрiї, виконуються описанi перетворення ПП, виписуються всi допустимi ПП та вiдповiднi дiаграми Фейнмана для масового оператора автоматично. Зрозумiло, що жодних iнших виразiв (дiаграм) для розглянутого наближення теорiї збурення не може бути побудовано.